Clean and efficient microwave-solvent-free conversion of homochiral amines, α-amino alcohols and α-amino acids to their chiral 2-substituted pyrrole derivatives - Aydogan, F; Demir, AS (PERGAMON-ELSEVIER SCIENCE LTD, 2005)
Efficient synthesis of 1,2-disubstituted homochiral pyrroles has been achieved by a two-component coupling of chloroenones and amine compounds on the surface of silica gel without any solvent under microwave irradiation. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: pyrrole; microwave; silica gel; chloroenone; PHOTOOXYGENATION; ACYLATION; CHEMISTRY; SYSTEMS